Ameliorative effect of gamma-aminobutyric acid on the antioxidant status and ammonia stress resistance of Micropterus salmoides - Zhenlu Wang; Qiong Zhou; Jiao Tu; Yizhou Wang; Rongqun Song; Zhipeng Chu; Shan Li; Junyi Li; Hui Zhang; Muzi Zhang; Jian Shao (Aquaculture Reports, 2023)
The effects of gamma-aminobutyric acid (GABA) on aquatic animals remain to be explored. Here, we conducted GABA addition tests, both in water and in feed, as well as ammonia stress tests using Micropterus salmoides (M. salmoides). The tissue structure and indicators associated with the oxidative state of M. salmoides were evaluated to assess the effects. The results showed that, the levels of alanine aminotransferase, alkaline phosphatase, and total antioxidant capacity in most of the GABA water addition groups were lower than those in the control group at 96 h after the addition of GABA. In the gill of feed addition groups (GL: 30 mg kg−1; GM: 90 mg kg−1; GH: 150 mg kg−1), the contents of glutathione (GSH) in the GH group were significantly higher when compared with their control group (CK group: 0 mg kg−1) at day 12 and day 15. In the following ammonia stress test, the tissue damage of the gill, brain, and kidney were alleviated in the GM and GH groups. The GSH contents of all tissues in all groups decreased gradually with the prolongation of the stress time. Conversely, the malondialdehyde (MDA) and nitric oxide (NO) contents have the opposite trend. The results suggested that GABA addition in water may not be applicable in actual aquaculture. The inclusion of GABA in the feed at concentrations of 90 and 150 mg kg−1 contributed to improving the ammonia resistance of M. salmoides by reducing tissue damage and the inflammatory response, as well as improving the antioxidant status. Moreover, the gill might be the target tissue protected by GABA in M. salmoides under ammonia stress. These results could enrich our basic understanding of the effect of GABA on aquatic animals and help us find possible ways to solve the environmental stress problems in aquaculture.